Uji Karakteristik Briket Berbahan Baku Tempurung Kelapa dengan Perekat Tepung Kanji Berdasarkan Variasi Ukuran Partikel dan Dimensi - Zuhri Diana; Mikhratunnisa Mikhratunnisa (Jurnal Teknologi Pangan dan Ilmu Pertanian, 2023)
The use of biomass as a renewable source for the development of bioenergy and biomaterials can also address the increasing needs of the community. Biomass is a more environmentally friendly alternative to oil and coal, which can replace non-renewable fuels. Biomass raw material with a high calorific value, is usually used as a mixing base or the main raw material in the manufacture of biobriquettes. The characteristics of briquettes made from coconut shell charcoal with starch adhesive are varied in dimensions and particle size of the charcoal. One of the adhesives that can be used to glue charcoal particles together to get compact briquettes is starch. This study aims to determine the effect of variations in the dimensions of charcoal and particle size used on the characteristics of briquettes made from coconut shell with starch adhesive. The method used was an experiment with Completely Randomized Design (CRD) testing three repetitions. The independent variables in this study were dimensional variations, namely cubes and pyramids, as well as variations in particle size using mesh 60, 80, and 100. The dependent variables in this study were the values of moisture content, ash content, destruction index, and heating value. From the results of testing a completely randomized design using ANOVA, it was found that the dimensions of the briquettes affected the ash content and flammability of the briquettes, while the particle size affected the moisture content, ash content, and flammability of the briquettes. Both dimensions and particle size have no effect on the briquette destruction index